Incidental Umbilical Hernias in Pilots: An Emerging Time Bomb or An Inconsequential Finding - CP Shanthanu; Snehangsh Dash; Umesh Kumar Mishra; MM Ram Shankar; Bhanu Pratap Singh (Journal of Medical Academics)
Aim and background: Umbilical hernias are defects in the ventral abdominal fascia occurring at or near the umbilicus. They occur commonly in populations worldwide, including civil aircrew. Our study was conducted at a premier civil aircrew evaluation center with 42 civil aircrew personnel diagnosed with incidental umbilical hernias. The aim of this study was to correlate the defect size of umbilical hernias with the prevalence of risk factors such as obesity and smoking. Methods: The methodology for selecting the 42 civil aircrews evaluated included aircrew who were over 18 years of age and had an umbilical hernia (i.e., hernia within 3 cm below or above the umbilical region). Personnel with other ventral/inguinal/childhood/multiple hernias, recurrent cases, or those with a history of any prior abdominal surgery were excluded from the study. Results: The results of our study yielded the fact that obese personnel were prone to developing large defect umbilical hernias. Conclusions: We have also tried to reach a middle ground regarding the rulings mentioned in the Manual for Civil Aviation of the International Civil Aviation Organization about the fitness of aircrew with umbilical hernias for flying duties. We have studied existing studies and also used our findings to conclude that medium-sized umbilical hernias (i.e., 1–4 cm defect) carry the least risk for complications and symptoms and hence may be permitted to fly with periodic surgical reviews. Clinical significance: The results of our study prove the relative safety of medium-sized umbilical hernias in the absence of risk factors such as smoking and obesity. These results, when supplemented by further high-volume center studies, if implemented into existing civil aviation policies, would further enable these aircrews to carry out aviation duties without affecting the administrative ability of flying agencies worldwide.